Angiographic and clinical characteristics of type 1 versus type 2 perioperative myocardial infarction. Issue 4 (9th March 2013) - Hanson, Ivan; Kahn, Joel; Dixon, Simon; Goldstein, James
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to analyze clinical and angiographic differences between the two etiologic subtypes of perioperative myocardial infarction (PMI). Background PMI is believed to occur by either reduced coronary blood flow attributable to acute plaque rupture and thrombosis (type 1) or primary increase in oxygen demand in the setting of stable but stenotic lesions (type 2). Incidence and mortality rates of PMI are substantial, but angiographic and clinical features are not well characterized. Methods Consecutive patients with PMI were classified as "type 1" or "type 2" based on angiographic characteristics of culprit lesions. Clinical and angiographic characteristics of each subtype were compared using statistical analyses. Results Of the 54 patients analyzed, 32 (59%) cases had type 1 PMI, whereas 22 others (41%) had type 2 PMI. Compared with type 2 patients, those with type 1 PMI more often had ECG (electrocardiogram) ST elevation (53% versus 23%, P = 0.026), greater peak troponin (15.3 ng/dl versus 5.3 ng/dl, P = 0.035), higher preoperative mean blood pressure (103 mm Hg versus 93 mm Hg, P = 0.009), greater decrease in mean intraoperative blood pressure (−36 mm Hg versus −26 mm Hg, P = 0.015). Type I patients trended toward greater in‐hospital mortality (16% versus 5%, P = 0.38) and length of hospitalization (13.5 days versus 9.0 days, P = 0.13). Conclusions These results demonstrate that PMI not only results from "demand ischemia" but also that in nearly 60% of cases the cause is acute plaque rupture. Patients with PMI attributable to plaque rupture suffer more intraoperative hypotension, greater transmural ischemia, larger infarct size, and trended toward worse outcome. © 2012 Wiley Periodicals, Inc.